Pension Provision of Russian Military in 19th - early 20th Century (by Material of Tobolsk Province) - L. N. Suslova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the study of the process of formation and evolution of the social security system for old age and disease of servicemen of the Tobolsk province in the 19th - early 20th centuries. The relevance of the chosen topic in connection with the modern reform of the pension system is shown. The study is based on the analysis of the complex of legislative, administrative and statistical sources of the State Archive in Tobolsk. Documentation of the funds of the provincial government of Tobolsk, the Tobolsk state chambers, etc. are used. Among them, an important place is occupied by the lists of pensioners living in the Tobolsk province, the sheets of the Tobolsk State Chamber on pensioners, documents fixing the number and amount of pensions issued and not issued, cases on the appointment of pensions. The legal framework of pension provision is analyzed. The author of the article points to the absence in the period under review of a single regulatory framework and pension practice common for all social categories of the population. Analyses of pension payments charged to the military personnel funds from the Treasury and savings from public aid funds for emeritus is made. It is concluded that the formation of pensions for military officials was completed by the end of the first quarter of the 19th century. The circle of persons entitled to receive a pension is defined, sources of pension financing are established. It is concluded that the pension provision of the military in the period under review was characterized by the consolidation of the principles of pension accrual at the legislative level, the dependence of the pension salary on the amount of annual salary, rank and length of military service.